Ultramorphology of eggshell of flesh fly Liosarcophaga dux (Diptera: Sarcophagidae) - Sukontason K.L. (2014)
Eggs of Liosarcophaga dux (Thomson) (Diptera: Sarcophagidae) are elongated and slightly bean-shaped, measuring ≈=1.5 mm in length. Each is covered externally by an eggshell comprised of polygonal patterns. In this study, scanning and transmission electron microscopy were used to examine the eggshell of this species of flesh fly for the first time. No plastron region or median area was detected. Ultrathin sectioning of the eggshell revealed multiple layers in the shell that could be observed using transmission electron microscopy.